TRANSPARANSI DAN AKUNTABILITAS ANGGARAN KELURAHAN: STUDI KASUS KELURAHAN KARANG REJO, KOTA TARAKAN - Noviyanti Angreani; Truly Wulandari; Iqrima Mas Mappangile; Olivia Pamilangan Andi’lolo (Hikamatzu | Journal of Multidisciplinary, 2025)
This study examines transparency and accountability in budget management at Karang Rejo Urban Village, Tarakan City, a non-SKPD (non–work unit) government entity without direct authority over public funds. Using a qualitative case study approach with data from in-depth interviews, the research found that fiscal management remains centralized and administrative, with accountability directed vertically to the City Government through Inspectorate audits. Transparency to the public is minimal, as financial information is not disclosed and digital systems like the Government Resource Management System (GRMS) are not yet implemented. Manual handling of Revolving Operational Funds (UP) further causes reporting delays and administrative errors. Key obstacles include regulatory limitations, inadequate human resources, and a lack of digital infrastructure. The study recommends institutional reform and the adoption of digital public information systems to improve community participation and enhance local fiscal governance